Advanced steam-explosion pretreatment mediated anaerobic digestion of municipal sludge: effects on methane yield, emerging contaminants removal, and microbial community - Balasundaram, Gowtham; Gahlot, Pallavi; Ahmed, Banafsha; Biswas, Pinakshi; Tyagi, Vinay Kumar; Svensson, Kine; Kumar, Vinod; Kazmi, Absar Ahmad (Elsevier, 2023)
Advanced steam explosion pretreatment, i.e., the Thermal hydrolysis process (THP) is applied mainly to improve the sludge solubilization and subsequent methane yield in the downstream anaerobic digestion (AD) process. However, the potential of THP in pretreating the high solids retention time (SRT) sludges, mitigating the risk of emerging organic micropollutants and effects on anaerobic microbiome in digester remains unclear. In this study, sludge from a sequencing batch reactor (SBR) system operating at a SRT of 40 days was subjected to THP using a 5 L pilot plant at the temperature ranges of 120–180 °C for 30–120 min. The effect of THP on organics solubilization, methane yield, organic micropollutant removal, and microbial community dynamics was studied. The highest methane yield of 507 mL CH4/g VSadded and volatile solids (VS) removal of 54% were observed at 160°C- 30min THP condition, i.e., 4.1 and 2.6 times higher than the control (123 mL CH4/gVSadded, 20.7%), respectively. The experimental values of hydrolysis coefficient and methane yield have been predicted using Modified Gompertz, First order, and Logistics models. The observed values fitted well with all three models showing an R2 value between 0.96 and 1.0. THP pretreated sludges showed >80% removal of Trimethoprim, Enrofloxacin, Ciprofloxacin, and Bezafibrate. However, Carbamazepine, 17α-ethinylestradiol, and Progesterone showed recalcitrant behavior, resulting in less than 50% removal. Microbial diversity analysis showed the dominance of Proteobacteria, Firmicutes, Chloroflexi, and Bacteroidetes, collectively accounting for >70–80% of bacterial reads. They are mainly responsible for the fermentation of complex biomolecules like polysaccharides, proteins, and lipids. The THP-mediated anaerobic digestion of sludge shows better performance than the control digestion, improved methane yield, higher VS and micropollutants removal, and a diverse microbiome in the digester.
Keywords: Thermal hydrolysis process (THP); Sewage sludge; Bio-methane; Micropollutants